Analisis Model Integrasi Sains dan Islam pada Pembelajaran IPA di SMP Negeri 05 Rokan IV Koto - Afiq Budiawan; Zahwa Riskina; Rian Vebrianto (Lembaga Anotero Scientific Pekanbaru, 2022)
The integration of science and Islamic religious values is needed in the reconstruction of the Islamic education system. This study aims to explore several models of integrating science and religion and their implications for Islamic education. The data obtained were analyzed and interviewed from several students at SMP Negeri 05 Rokan IV Koto. Based on the results of the study, it can be concluded that the integration of science and Islam in learning only a few students know and some of them still think that science and religion cannot be used as one in learning. Therefore, the results of this study can be used as information for educators and further researchers to overcome the low understanding of students in understanding the integration of science and Islam.